Validation of Mineral (Fe, Zn, and Cu) Analysis Methods in Carbohydrate, Protein and Fat-Rich Samples Using Microwave Digestion Method - Didah Nur Faridah; Imas Solihat; Nancy Dewi Yuliana (Indonesian Journal of Chemistry, 2020)
Destruction process using both dry and wet conditions serves as a significant step in mineral quantification. Wet destruction using microwave-assisted digestion refers to the standard method of AOAC (2012); in this work, we modified the destruction procedures provided in microwave digestion manual book, including temperature, reagent volume (HNO3 and H2O2), and length of destruction. The experiment works aimed (1) to validate the procedures in destruction process using microwave digestion; (2) to quantify Fe, Zn and Cu in various food matrices (canned peas, canned fish, full cream powdered milk) using a validated method. The method was evaluated according to linearity, accuracy, precision, absolute and relative LOD, LOQ, and intra-reproducibility. Measurement of Fe, Zn and Cu were considered to have a satisfying accuracy at a range of 80–115%, with a good precision value (% RSD < 2/3 CV Horwitz), while regression curves R2 > 0.995. The results showed that data collected from the modified method was not significantly different compared to those from the AOAC method. The currently developed method also fulfilled the acceptability requirements for laboratory analysis.